Detection of Black Hole Attack in MANETS Using IDSAODV and Reverse AODV - ليلى, اناس; محمد, منى (Latakia University Journal -Engineering Sciences Series, 2021)
Black Hole Attack is one of the most dangerous and most common security attacks in MANET networks, so researchers have been directed to find techniques to discover this attack, Intrusion Detection System AODV(IDSAODV) and Reverse AODV are two of these techniques. In this research, we studied the effect of Black Hole Attack on network performance in the presence of one or more attackers. then we applied IDSAODV and Reverse AODV in network to evaluate their effectiveness in detecting the attack and mitigating its effects. We used Throughput, Packet delivery ratio (PDR) and Normalized routing load(NRL) to performance evaluation. The results of the extensive simulation showed that the IDSAODV application reduced the impact of the attack ,where it increased the packet delivery rate up to 68%, while Reverse AODV provided better results where the PDR reached to 100 % , but it caused increase in NRL in comparison by IDSAODV. The simulation results also showed that the performance of the IDSAODV was affected by the location of the attacking node.